BUSINESS MODEL INNOVATION TOWARDS CORPORATE ENTREPRENEURSHIP AT REGIONAL DRINKING WATER COMPANY TIRTA MAYANG JAMBI CITY - Rendi Aditya Alfanza; Fitriaty Fitriaty; Tona Lubis (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
This study aims to find out how the Business Model Innovation with its 3 (three) value creation elements Value Proposition, Value Creation, and Value Capture Innovation is able to foster entrepreneurial activity in the Regional Drinking Water Company Tirta Mayang as a monopoly company for clean water management in Jambi City. Entrepreneurial activity is a characteristic of Corporate Entrepreneurship that influences company performance. Business Model Innovation uses 3 (three) dimensions, namely diversification, technology, and good corporate governance. This research was conducted using quantitative methods, primary and secondary data sources using questionnaire research instruments and Partial Least Square (PLS) data analysis techniques with a total sample of 73 people. The results of this study provide knowledge on how a relevant Business Model Innovation can maintain the Sustainability of local companies that are transforming towards Corporate Entrepreneurship in an effort to increase profitability and decent quality of clean water services as a form of global commitment from the Sustainable Development Goal's (SDGs).